Exchange rate, inflation rate, expectations, and the demand for money: Germany 1970 - 1978 - Hans-Edi Loef (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1980)
This paper analyses the influence of exchange rate expectations on the demand for real balances. It is shown that currency substitution is an important factor in explaining real money holdings in Germany from 1970 to 1978. Additionally, evidence is provided concerning the influence of the expected inflation rate (approximated by the actual rate) on money demand. The empirical analysis indicates that domestic and foreign bonds are very close substitutes and that domestic and foreign interest rates can be used interchangeably as the opportunity coats of holding real balances. As alternatives to money as a means of holding wealth, domestic goods and bonds are closer substitutes than foreign bonds and money.
Keywords: 330